DEVELOPING ENGLISH SPEAKING MATERIALS FOR STUDENTS OF BEAUTY STUDY PROGRAM AT VOCATIONAL SCHOOL - Eka Winda Sari and Sortha Silitonga (REGISTER: Journal of English Language Teaching of FBS-Unimed, 2018)
This study aims to develop appropriate English speaking materials for grade X students of  Beauty Study Program at SMK Negeri 1 Beringin. This study was conducted by Research and Development (R & D) design through six phases; gathering information and data, analyzing data, designing new materials, validating new materials by experts, revising, and final product. The subject of this research was grade X students of Beauty study program consisting of 19 students. The instrumentations for collecting data were questionairre and interview. After analyzing the data, the writer got the students’ needs. The data were gathered by administering interview to the teacher and distributing the questionairre to 19 respondents to get the students’ needs. The result of questionairre and interview prove that the students need English speaking materials which appropriate to their major that is Beauty study program. Thus, developing English speaking materials consist of three units, they are welcome to our beauty salon, complimenting and showing care, and congratulations on your achievement. The products have been validated by experts. The average scores are 4.3 from English Lecturer and 4.5 from English Teacher. It means that the developing materials categorized as relevant or appropriate for Grade X Students of Beauty study program.